The Mediating Role of Psychosocial Benefits in the Satisfaction Formation Process - Olaf Prevo; Patrick Leunisse; Henk Roest (Tinbergen Institute, 1999)
In this paper we investigate the mediating role of psychosocial benefits in the customersatisfaction/dissatisfaction formation process. Most research on this subject deals with thecausality direction of psychosocial benefits and satisfaction, sometimes preceded by anoverall functional benefit construct. We focus on the relationships of specific functionalbenefits and psychosocial benefits within a customer satisfaction framework. Knowledge ofwhich functional benefit can control which psychosocial benefit directly enables themanagement of customer satisfaction and indirectly purchase intention. Using Partial LeastSquares, we find interesting relationships in the restaurant business.
Keywords: 330; service quality; psychosocial benefits; satisfaction; Dienstleistungsqualität; Beziehungsmarketing; Nutzen; Gastronomie; Theorie; Niederlande